ROLE OF THE WATER BUFFALO IN RURAL LIVELIHOODS IN ASIA AND CHALLENGES FOR FUTURE RESEARCH TO IMPROVE REPRODUCTIVE EFFICIENCY AND PRODUCTIVITY - Perera, B. M. A. Oswin (Proceeding Buffalo International Conference, 2013)
The buffalo (Bubalus bubalis) has been used as a multi-purpose animal in Asia since pre-historic times and is still playing an important role in the livelihoods and welfare of smallholder livestock producers in the region. It has the unique ability to survive in stressful environments, feed on poor quality forages and provide milk rich in butterfat and proteins, while providing draught power and manure for crop agriculture. However, with increased land-use intensity for crop production and human settlements, only marginal and poor quality lands are left for grazing and mixed farming. Consequently, many farming systems under which buffalo are raised involve harsh environments, lack of year-round feed supply and minimal managerial inputs, which compromise their reproductive efficiency and overall productivity. However, studies have shown that they can have good fertility if they are managed and fed properly so as to overcome such stresses. There is thus a need to introduce improved technologies in breeding, reproductive management and nutrition to the smallholder farmers. Such technologies must be practicable, cost-effective and sustainable using the locally available resources. This requires active farmer participatory programmes in technology generation as well as technology transfer, to promote integrated farming systems that use buffalo as a multi-purpose animal. In the subsistence extensive farming systems that are constrained by lack of land and traditional feed resources, the farmers need to be provided the knowledge, skills, technical services and marketing support to enable them to adopt more commercial and semi-intensive systems of buffalo production. The objective of this paper is to discuss some of the current constraints to buffalo production and reproductive efficiency in rural farming systems in Asia, and to identify the needs and challenges for future research to address these limitations.